Short message service (SMS) and its applications - Ismail, M.A.; Md-Noor, R.; Othman, M. (2004)
The use of short message service (SMS) has grown tremendously in the past few years. Billions of users use this service to send text messages. Various applications have been introduced by service providers, e.g., mobile banking, summons checkpoint, SMS chat, etc., all of which have become a huge success. This chapter gives an overview of how this service is provided and discusses various SMS applications offered to the user. We explore the reasons behind its success and the issues that must be addressed to provide these applications. We also examine future trends and the challenges that must be overcome in order to enhance this service. We hope that this chapter gives a better understanding of how SMS applications are provided and what may be expected in future applications given the enhancement on the current SMS and technology advancement.